COMPARISON OF TWO ASPHALT MIXTURES USING COMPLEX MODULUS TEST IN LIBYAN WEATHER - El atrash, Khlifa Saad; Assaf, Gabriel J. (Journal of Civil Engineering, Science and Technology, 2019)
The complex modulus test is dependent on temperature and loading frequency. Thus, the results produced from this test will give a more accurate representation of traffic load effects on asphalt pavement. Laboratory experiments were conducted on two different asphalt mixtures for road research projects (Libya/Roads). All specimens had the same mixtures of aggregate gradation GB-20 incorporated with two different asphalt binders PG70-10 and B (60/70). To obtain the master curve, there were some errors at low temperatures (-25, -10 ºC) and high temperature (54 ºC), so these values were discarded. In addition, 2-complex modulus (CM) and phase angles (Phi) in the test were measured at temperatures of -25, -10, -5, 10, 25, 35, and 54ºC, as well as frequencies of 25, 10, 5, 1, 0.5 and 0.1 Hz. The results displayed the influence of the type of binder on the rheology of the mixtures and gradation on the intensity. Hence, using binder PG 70-10 in Libyan asphalt roads may reduce the binder content, increase the mixture workability, and decrease the thermal cracking. The intrinsic characteristics related to binder properties and weather temperature exhibited the most significant impact on the predicted dynamic modulus.